FASTER: an unsupervised fully automated sleep staging method for mice. (28th April 2013) - Sunagawa, Genshiro A.; Séi, Hiroyoshi; Shimba, Shigeki; Urade, Yoshihiro; Ueda, Hiroki R.
<x xml:space="preserve">Abstract</x> Identifying the stages of sleep, or sleep staging, is an unavoidable step in sleep research and typically requires visual inspection of electroencephalography (EEG) and electromyography (EMG) data. Currently, scoring is slow, biased and prone to error by humans and thus is the most important bottleneck for large‐scale sleep research in animals. We have developed an unsupervised, fully automated sleep staging method for mice that allows less subjective and high‐throughput evaluation of sleep. Fully Automated Sleep sTaging method via EEG/EMG Recordings (FASTER) is based on nonparametric density estimation clustering of comprehensive EEG/EMG power spectra. FASTER can accurately identify sleep patterns in mice that have been perturbed by drugs or by genetic modification of a clock gene. The overall accuracy is over 90% in every group. 24‐h data are staged by a laptop computer in 10 min, which is faster than an experienced human rater. Dramatically improving the sleep staging process in both quality and throughput FASTER will open the door to quantitative and comprehensive animal sleep research.